2008
DOI: 10.1111/j.1474-9726.2008.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila lifespan control by dietary restriction independent of insulin‐like signaling

Abstract: SummaryReduced insulin/insulin-like growth factor (IGF) signaling may be a natural way for the reduction of dietary nutrients to extend lifespan. While evidence challenging this hypothesis is accumulating with Caenorhabditis elegans , for Drosophila melanogaster it is still thought that insulin/IGF and the mechanisms of dietary restriction (DR) might as yet function through overlapping mechanisms. Here, we aim to understand this potential overlap. We found that over-expression of dFOXO in head fat body extends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
189
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(203 citation statements)
references
References 31 publications
12
189
2
Order By: Relevance
“…Dietary restriction (DR) increases lifespan in diverse organisms, including Drosophila (4) where the increased longevity from DR is dFOXO-independent (18). Interestingly, we found that flies subjected to DR were not resistant to DDT (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Dietary restriction (DR) increases lifespan in diverse organisms, including Drosophila (4) where the increased longevity from DR is dFOXO-independent (18). Interestingly, we found that flies subjected to DR were not resistant to DDT (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Min et al . (2008) showed evidence that the diet‐dependent effects of dFoxO overexpression on fly's lifespan are associated with reduction of dilp2.…”
Section: Animal Modelsmentioning
confidence: 99%
“…The state of insulin signaling provides one measure of the nutritional status of the fly. Under conditions of a nutrient challenge, such as CR, insulin signaling is decreased (17,22). An indirect method for assessing the state of insulin signaling is the level of mRNA expression for the 3 Drosophila insulin-like peptides (Dilps) found in the neurosecretory insulinproducing cells (IPCs) of the brain: Dilp2, Dilp3, and Dilp5.…”
Section: Decreases In the Calorie Content Of Food Induce A Decrease Imentioning
confidence: 99%
“…In nematodes, long-lived daf-2/InR and daf-16/dFOXO mutants live even longer when subject to CR (16). In flies, knockdown of dilps using RNAi does not decrease the life span-extending effects of CR and dFoxO null mutations continue to have a CR responsive life span extension, suggesting that CR and IISmediated life span extension may be unrelated (17). However, CR fails to further increase the life span extension of long-lived chico (InR substrate) mutant flies, suggesting CR and IIS mediated life span extension may be related (18).…”
mentioning
confidence: 99%